Exophytic Osteochondroma of the Brow. Issue 6 (November 2017) - Jakobiec, Frederick A.; Zakka, Fouad R.; Lee, Nahyoung Grace
Abstract : Most bony and cartilaginous lesions of the orbit and periorbital compartments are benign, grow endophytically, and are composed of dense lamellar bone (eburnated or ivory osteomas). An 87-year-old woman had a well-circumscribed, firm, round, and exophytic lesion of the brow region for at least 15 years. Excisional surgery disclosed an osteocartilaginous lesion with an enveloping pseudocapsule (periosteum/perichondrium) and a narrow stalk connecting it to the frontal bone. The periphery of the lesion displayed lamellar bone which appeared to be replacing a central cartilaginous zone. The adjacent deep preaponeurotic fat displayed nodules of collagen with myxoid change and occasional CD34 + spindle cells suggestive of a spindle cell lipoma. Because of the osteochondroma's deep location in the preaponeurotic fat, the lesion differs from an osteoma cutis found in the dermis which fails to exhibit a cartilaginous component or a periosteum. Other clinically simulating lesions are described. Abstract : Among lesions of the brow region such as pilomatrixoma, lipoma, cysts, chondroid syringoma, and osteoma cutis, an osteochondroma located in the deep preaponeurotic fat should also be considered.